2009
DOI: 10.1086/600099
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriolytic Activity in the Ejaculate of an Insect

Abstract: The rapid evolution of ejaculate components is considered to be largely driven by sexual selection. Less attention has been paid to the fact that sperm and microorganisms frequently meet; we consequently predict selection for substances that protect a male's ejaculate. We report, for the first time, bacteriolytic activity (lysozyme-like immune activity [LLA]) in the ejaculate of an animal, the common bedbug Cimex lectularius. We also show that in almost half the males LLA in the seminal fluid exceeded LLA in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 25 publications
2
72
0
Order By: Relevance
“…Host-parasite interactions in reproductive tissues and secretions has received relatively little scientific attention in insects but have been studied in vertebrates [7], where it is suggested that proteins with antimicrobial functions within the ejaculate are of central importance for male fitness because they suppress microbial growth [8,9] and affect sperm motility [10]. Antimicrobial proteins in ejaculates have also been reported in insects [5,6,[11][12][13], and antimicrobial activity of seminal fluid in the bedbug Cimex lectularius reduces sperm mortality in vitro [13,14]. However, the functioning of antimicrobial molecules in ejaculates or in the female's sexual tract or their influence on male and female reproductive success in insects have not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Host-parasite interactions in reproductive tissues and secretions has received relatively little scientific attention in insects but have been studied in vertebrates [7], where it is suggested that proteins with antimicrobial functions within the ejaculate are of central importance for male fitness because they suppress microbial growth [8,9] and affect sperm motility [10]. Antimicrobial proteins in ejaculates have also been reported in insects [5,6,[11][12][13], and antimicrobial activity of seminal fluid in the bedbug Cimex lectularius reduces sperm mortality in vitro [13,14]. However, the functioning of antimicrobial molecules in ejaculates or in the female's sexual tract or their influence on male and female reproductive success in insects have not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Tm-485, assembled from three ESTs, is 47% identical to a Gryllus accessory gland protein and may represent an antimicrobial peptide. 87 Tm-138 is 57% identical to insect proteins having the pheromone binding domain.…”
mentioning
confidence: 99%
“…8739) and S. aureus (ATCC no. 6538P) using a liquid growth inhibition assay modified from Otti et al ( [9]; see the electronic supplementary material). Briefly, semen samples were diluted 1 : 1 with Tryptic Soy Broth (TSB; no.…”
Section: Methodsmentioning
confidence: 99%